The Effect of Digital Transformation on Manufacturing Enterprise Performance - Di Wang; Xuefeng Shao; Yang Song; Hualu Shao; Longqi Wang (Amfiteatru Economic, 2023)
Recent evidence indicates that the proportion of manufacturing enterprises undergoing digital transformation and the digital investment made by manufacturing enterprises are increasing, suggesting that digital transformation may affect the production and operation of manufacturing enterprises. This paper investigates the influence of digital transformation on the performance of manufacturing enterprises and the intermediary effect of efficiency and costs. We take the annual reports of 156 listed Chinese manufacturing enterprises from 2015 to 2019 as samples for data collection and apply the textual analysis method to build the digital transformation index of manufacturing enterprises. Our analysis shows that the digital transformation of manufacturing enterprises plays a positive role in improving enterprise performance. Based on the path analysis, digital transformation indirectly improves the performance of the manufacturing enterprise by improving operational efficiency and reducing production costs. We also found that the level of digital transformation is related to the performance of Chinese manufacturing enterprises. A relatively low level of digital transformation does not have a significant impact on the performance of the Chinese manufacturing enterprise. However, medium and high levels of digital transformation will significantly increase the performance of manufacturing enterprises. Our study contributes to providing new ideas to construct enterprise digital transformation indicators. We also offer new insights into different levels of enterprise digital transformation on enterprise performance.
Keywords: D22; D24; L25; 330; Digital transformation; enterprise performance; textual analysis; manufacturing enterprise.